THE SYSTEM-DYNAMIC MODEL OF EARLY REPAYMENT OF MORTGAGE CREDITS: RISKS AND PROFITABILITY - Vasiliy M. Kartvelishvili; Anna V. Nikolaeva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with key points of the mortgage securities analysis. The system-dynamic model of early repayment of credits included in mortgage cover was developed. The model allows to assess the impact of the speed of early repayment on appeal of securities and to find out principle risks which the mortgage securities investor faces. With the help of the model the authors analyze the real speed of early repayment of credits included in mortgage cover of securities issued on Russian market and find key causes of the speed altering. The prospects of developing the Russian market of secondary mortgage crediting in the near future were reviewed. It was shown that the analysis can be taken into account by Russian investors interested in long-term investment with max profitability. The system-dynamic model designed by the authors will allow the potential investors to analyze the appeal of certain mortgage securities on the basis of the information about the source of cash payments (mortgage pull).